Dynamic reconfiguration of three-phase unbalanced distribution networks. (July 2018) - Zhai, H.F.; Yang, M.; Chen, B.; Kang, N.
Highlights: A novel dynamic DNR approach of unbalanced distribution networks is proposed. The model considers the time-varying nature of loads and DG output. The model considers the three-phase voltage imbalance and power imbalance. Several linearizing methods are used to convert the DNR problem into a MILP model. Abstract: The increasing penetration of distributed generations (DGs) and variable loads introduces significant power fluctuations to distribution networks, rendering conventional reconfiguration strategies ineffective. In the context of an active distribution network (ADN), remote control switches can be operated in real time through a centralized control scheme. Therein the distribution network topology can be configured in a flexible and dynamic manner capable of adapting to time-varying load demand and DG output. This paper presents a dynamic reconfiguration approach for a three-phase unbalanced distribution network. The ADN topology is optimized for the look-ahead time periods and is adaptive to the time-varying load demand and DG output while minimizing the daily power loss costs. To improve the calculation efficiency, several linearization methods are introduced to formulate the dynamic reconfiguration as a mixed-integer linear programming problem, which can be effectively solved using off-the-shelf solvers. The effectiveness of the proposed approach is verified by the test results obtained on a modified IEEE 34 node test feeder.